Microwave ablation compared with hepatic resection for the treatment of hepatocellular carcinoma and liver metastases: a systematic review and meta-analysis - Mrudula B. Glassberg (World Journal of Surgical Oncology, 2019)
Abstract Background Hepatic resection (HR) is the gold standard liver cancer treatment, but few patients are eligible due to comorbidities or tumor location. Microwave ablation (MWA) is an important complementary liver cancer treatment to HR. This systematic review compared MWA with HR for liver cancer treatment. Methods A systematic search of MEDLINE, EMBASE, and CENTRAL was conducted for randomized and observational studies published from 2006 onwards. The primary outcome was local tumor recurrence (LTR), and a random effects model was used for meta-analyses. Results Of the 1845 studies identified, 1 randomized and 15 observational studies met the inclusion criteria. LTR was significantly increased with MWA versus HR (risk ratio (RR) = 2.49; P = 0.016). In secondary measures, HR provided significantly higher 3- and 5-year overall survival (RR = 0.94; P = 0.03 and RR = 0.88; P = 0.01, respectively) and 3-year disease-free survival (RR = 0.78; P = 0.009). MWA exhibited significantly shorter length of stay (weighted mean difference (WMD) = − 6.16 days; P < 0.001) and operative time (WMD = − 58.69 min; P < 0.001), less intraoperative blood loss (WMD = − 189.09 mL; P = 0.006), and fewer complications than HR (RR = 0.31; P < 0.001). When MWA was combined with HR and compared with either modality alone, complications and blood loss were significantly lower with the combination treatment; however, there were no differences in other outcomes. Subgroup and sensitivity analyses were generally aligned with the main results. Conclusions MWA can be an effective and safe alternative to HR in patients/tumors that are not amenable to resection. More randomized and economic studies should be performed that compare the two treatments, especially to determine the target population that benefits most from MWA.